Classification of Types of Crimes Against Human Physique Using the K-Means Clustering Method - Rizkah Fadillah; Fiqri Hidayat Rangkuti; Anggi Jaya Maulana Siregar; Rizky Ananda; Muhammad Syahrizal (Jurnal Ilmu Komputer, Teknologi Dan Informasi, 2025)
Human physical crimes are unlawful acts and prohibited by the rule of law, which can harm or damage the body of others. This study aims to examine the number of groupings of types of crimes against human physique in 2019 to 2020 in all areas of East Nusa Tenggara province. To do this, we use the K-Means Clustering method to group the types of physical crimes against humans. The data used came from the Central Statistics Agency of East Nusa Tenggara province. The K-Means method is one of the non-hierarchical data clustering methods that seeks to partition data into the form of one or more clusters/groups. After the application of the K-Means algorithm in the grouping of types of crimes against human bodies in 2019 to 2020 in the East Nusa Tenggara region, there are 3 centroids, C1 for areas with low crimes, C2 for areas with moderate crimes and C3 for areas with high crimes. The initial centroid value is determined randomly and then for the next centroid is adjusted to the result of the calculation of the closest distance (minimum). The final results obtained are areas with low crime totaling 13 regions, namely East Sumba, Lembata, Sikka, Ende, Ngada, Manggarai, Rote Ndao, West Manggarai, Central Sumba, Southwest Sumba, Nagekeo, East Manggarai, and Sabu Raijua. There are 7 areas with moderate crimes, namely West Sumba, Kupang, South Central Timor, North Central Timor, Belu, Alor, and East Flores. As for the area with high crime, there is 1 area, namely Kupang City.